Math virtual assistant

About Snapxam Calculators Topics Go Premium
ENGESP
Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

\sqrt{-x^2}+x\sqrt{9}-\sqrt{-16x^2}=0

Solve the equation x9^0.5-1(-16x^2)^0.5+(-1x^2)^0.5=0

Answer

$x_1=0$,\:$false$

Step-by-step explanation

Problem

$\sqrt{-x^2}+x\sqrt{9}-\sqrt{-16x^2}=0$
1

The power of a product is equal to the product of it's factors raised to the same power

$-1\cdot \sqrt{-16}\sqrt{x^2}+3x+\sqrt{-1}x=0$

Unlock this step-by-step solution!

Answer

$x_1=0$,\:$false$